'We are Different': do Anti-establishment Parties Promote Distinctive Elites? An Analysis of the Spanish Case. Issue 1 (2nd January 2021) - Tarditi, Valeria; Vittori, Davide
ABSTRACT: Since the Great Recession, new parties challenged the pre-eminence of mainstream parties in many European democracies. In this paper we wonder to what extent this challenge translates in the representative politics. This paper aims to evaluate whether a) in terms of descriptive representation, the new challenger parties renewed the composition of the Parliaments; b) new challenger parties belonging to different ideological families elect different élites. The analysis focuses on two new successful anti-establishment parties: Podemos and Ciudadanos. Podemos belongs to the radical left family while Ciudadanos is a centre-right liberal party. We have built a dataset of the representatives of these two parties and the two other mainstream parties (PP and PSOE) in the Congress (2016), in the Autonomous Communities (2015) and in the Party in Central Office. Our findings suggest that Podemos and C's elites are younger and better educated compared to mainstream parties. Yet, we found that beyond their common anti-establishment background, different core ideologies matter when it comes to other aspects of the descriptive representation: in terms of education and working background, Podemos and C's élites are more similar to their ideologically closer parties, rather than among each other, thus highlighting the irrelevance of the shared anti-establishment rhetoric.